2022
DOI: 10.36440/recmvz.v20i1.38221
|View full text |Cite
|
Sign up to set email alerts
|

Teste de Letramento Funcional em Saúde Animal – LFSA

Abstract: O Letramento Funcional em Saúde (LFS) é um dos determinantes sociais estabelecidos que indica a capacidade de se obter, analisar e aplicar as informações médicas, no entanto, ainda não existe um formulário aplicado à Medicina Veterinária. No presente trabalho, foi criado um teste de Letramento Funcional em Saúde Animal (LFSA) para ser avaliada a compreensão de tutores de cães e gatos a respeito de informações comumente utilizadas nas prescrições veterinárias. Apesar de entenderem as orientações verbais, 62% tê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Because it has a diversified diet, the species needs anatomical and habitual characteristics that help it to obtain its meals. Such aspects have already been described in works that addressed morphological aspects of the stomach (Cavalcante et al, 2021) and the tongue (Silva et al, 2015) and reported adaptive changes that this animal has due to diet and metabolism (Ferigolo, 1985;Nogueira et al, 2014).…”
Section: Introductionmentioning
confidence: 68%
“…Because it has a diversified diet, the species needs anatomical and habitual characteristics that help it to obtain its meals. Such aspects have already been described in works that addressed morphological aspects of the stomach (Cavalcante et al, 2021) and the tongue (Silva et al, 2015) and reported adaptive changes that this animal has due to diet and metabolism (Ferigolo, 1985;Nogueira et al, 2014).…”
Section: Introductionmentioning
confidence: 68%